Differences In Tolerance of Students and General Society Based on Religious Identity Politics: A Literature Study - Sembodo, Dimas Prio; Nurmina (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Identity politics is inseparable from multicultural society. Identity politics is a form of political method used by various majority and minority groups to achieve the desired ideal political goals. Due to differences in ideal views held between groups, the use of identity politics by majority groups to accommodate political interests often leads to conflict because it threatens the interests of minority groups and vulnerable groups such as religious, ethnic and gender groups. Based on the level of use, identity politics is used at the level of social life up to the level of student life to fulfill various political goals such as attracting votes in the election of leaders and the identity politics that is often used is religious identity politics. The majority of the people of West Sumatra are adherents of the Islamic faith, the use of Islamic identity politics often threatens the existence of other ethnicities and beliefs through sharia regional regulations. In student life, identity politics is related to everyday life, including fulfilling the need to worship according to beliefs and the need for mutual respect between students so that a harmonious multicultural life is achieved. The method that will be used in this research is a literature review, is by analyzing various research articles related to political tolerance and religious identity politics. The results of this research show that there are indications of differences in political tolerance between society and students in West Sumatra related to religious identity politics.